2019
DOI: 10.1155/2019/5413461
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Steatosis (NAFLD) and Steatohepatitis (NASH) Exhibit Hepatic Lobe-Specific Gelatinases Activity and Oxidative Stress

Abstract: Animal models of obstructive cholestasis and ischemia/reperfusion damage have revealed the functional heterogeneity of liver lobes. This study evaluates this heterogeneity in nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) rat models. Twelve-week-old Obese and Lean male Zucker rats were used for NAFLD. Eight-week-old male Wistar rats fed with 8-week methionine-choline-deficient (MCD) diet and relative control diet were used for NASH. Gelatinase (MMP-2; MMP-9) activity and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…We found hepatic TBARS concentration to be significantly higher in the CDAHFD groups than in the ND groups. This is consistent with an increase in the liver reactive oxygen species and TBARS concentrations in other studies on NASH models (6,7,23,24). In contrast, we could partly observe the expected increase the levels of TBARS in the mice with renalase KO.…”
Section: Discussionsupporting
confidence: 92%
“…We found hepatic TBARS concentration to be significantly higher in the CDAHFD groups than in the ND groups. This is consistent with an increase in the liver reactive oxygen species and TBARS concentrations in other studies on NASH models (6,7,23,24). In contrast, we could partly observe the expected increase the levels of TBARS in the mice with renalase KO.…”
Section: Discussionsupporting
confidence: 92%
“…In relation to TIMPs dysregulation in obese adipose tissue, it has been observed an increase of TIMP-1 and -2 in patients with metabolic syndrome and diabetes [53]. In fact, these two enzymes may be considered as markers of non-alcoholic fatty liver disease (NAFLD) [69,70,71]. On the one hand, the authors reported an increase TIMP-1 levels in the serum of patients with gestational diabetes mellitus [72] and patients with obesity and cardiovascular risk [63].…”
Section: Structure Of Extracellular Matrix In the Adipose Tissue Amentioning
confidence: 99%
“…The MMPs are zinc‐dependent endopeptidases that participate in the extracellular matrix (ECM) remodeling. The activity of MMP‐2 and MMP‐9 has been noted to increase in the early‐stage liver disease itself and the inflammatory period of NASH (D’Amico et al, ; Palladini et al, ). In the present study, nutrient mixture supplementation has reduced MMP‐9 in NASH animals and these findings are consisting of reduced Sirius red positivity for fibrosis.…”
Section: Discussionmentioning
confidence: 99%